A qualitative analysis of GRI principles for defining sustainability report quality: an Australian case from the preparers' perspective. Issue 4 (1st October 2020) - Safari, Maryam; Areeb, Amreen
ABSTRACT: This paper aims to analyze how sustainability report preparers perceive the Global Reporting Initiative's (GRI) Principles for Defining Report Quality and explore the opportunities, challenges and influential factors that report preparers experience in the application of these principles. Underpinned by a critical agenda, this study brings together an exploratory approach and a thematic analysis of qualitative data derived from in-depth semi-structured interviews with key individuals closely involved in the preparation of sustainability reports. The global recognition of GRI reporting offers a context that allows the findings to be applicable to stakeholders worldwide. The study's major findings indicated that under-developed reporting systems, along with time and cost constraints, have served as prominent barriers to efficient practicalization of the Principles for Defining Report Quality . The findings provide exemplars and suggestions on good sustainability reporting practices, such as digitalization of organizations' supply-chain management, communication strategies and stakeholder relation mechanisms, and explain advantages of transition to two-way communication strategies that enable sensemaking and sensegiving conjointly.